Analisis Filsafat Ilmu Keolahragaan dan Rekonstruksi Nilai Sportivitas dalam Peristiwa Kanjuruhan - Laras Fadhilah Putri; Sumaryanto; Sumarjo; Satya Perdana (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aims to analyze the nature of sports science and the deviation of sportsmanship values in the Kanjuruhan Tragedy through the perspective of philosophy of science. The focus of the study is directed at three philosophical foundations, namely ontology, epistemology, and axiology, to understand the gap between the ideal concept of sports and the reality of match organization practices. This study employs a qualitative descriptive design using a literature review approach. Data were gathered from scientific journals, official reports, regulations, and other documents relevant to the research focus. The collected information was analyzed through several stages, including data reduction, data display, and drawing conclusions. The findings reveal that the three philosophical foundations of science in the field of sports have not yet been consistently reflected in real sports practices. Ontologically, sports have been narrowed down to mere competition. Epistemologically, scientific knowledge about safety and match management is not optimally applied. Axiologically, moral values such as sportsmanship, fair play, and respect for human dignity are not well internalized. The Kanjuruhan tragedy is clear evidence of the discrepancy between the ideal concept of sports and the reality on the field. The deviation from the value of sportsmanship, the excessive use of force by the police and the Indonesian National Armed Forces, weak match management, and the large number of casualties show that human values and the basic principles of sports have not been made the main foundation. Therefore, there is a need to strengthen the philosophical foundation of science, improve scientific competence, and internalize moral values to realize safe, ethical, and humane sports practices in accordance with the essence of sports science.